Implementasi Pemeriksaan Thoracolumbal pada Kasus Kifosis Proyeksi Ap/Lateral dengan Memperhatikan Keamanan dan Kenyamanan Pasien: Penelitian - Dewi Febriyanti; Pocut Zairiana Finzia; Fikri Rahmad Akbar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine how the implementation of thoracolumbar examination in cases of AP/Lateral projection Kyphosis by considering the safety and comfort of patients at Meuraxa Regional General Hospital, Banda Aceh City and analyze the results of the implementation of Thoracolumbar examination in cases of AP/Lateral projection Kyphosis by considering the safety and comfort of patients at Meuraxa Regional General Hospital, Banda Aceh City. This study is a descriptive study by collecting several data sources in the form of interviews and literature studies. The objects in this study were patients with complaints of Kyphosis. From the results of the study, two images were obtained that can provide a clear picture in terms of results, detail, sharpness, density and contrast are also very good, but in terms of safety and comfort for the patient itself, special attention is needed. Further research is expected to pay attention to several things, namely object thickness, exposition factors, cassettes, markers, the right distance size and reducing object movement when photographed by considering the safety and comfort of patients.